Malignant Transformation of Unknown Duration of an Ovarian Mature Cystic Teratoma Presenting as a Trocar Recurrence in a Young Patient: A Case Report and Literature Review - Tomohiro Okuda; Yoko Uda; Shiho Sakai; Taishi Harada (Case Reports in Obstetrics and Gynecology)
Although laparoscopic cystectomy is a safe and effective management strategy for ovarian mature cystic teratoma (MCT) in pediatric and adolescent patients, it has been challenged because of its association with a higher risk of intraoperative spillage leading to chemical peritonitis, adhesion formation, and iatrogenic implantation of malignant cells. Here, we report a rare case of a 23-year-old female patient with MCT tissue during laparoscopic ovarian cystectomy that remained in the peritoneum, possibly becoming malignant thereafter. Intraoperatively, the cyst’s contents leaked into the abdominal cavity. The abdominal cavity was thoroughly cleaned before the operation was completed. Pathological examination revealed an MCT without malignant findings. The patient’s postoperative course was uneventful. Although the excised tissue was benign, the patient presented with a mass at the trocar wound (upper suprapubic area) 2 years after initial surgery. Biopsy results indicated squamous cell carcinoma. Moreover, peritoneal and bladder invasions were diagnosed. She subsequently experienced symptoms of cancerous peritonitis. Achieving a complete cure through surgery alone was deemed difficult; however, successful neoadjuvant chemotherapy and tumor reduction surgery kept her alive up until the publication of this case report, 3 years since diagnosis with squamous cell carcinoma. This case indicates that malignant transformation of MCTs can occur at any age.